PENGARUH KEPUASAN KOMPENSASI TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN AFEKTIF SEBAGAI VARIABEL INTERVENING (Studi Pada Karyawan PTSuara Merdeka Semarang) - Fajar, Akhmad; Ratnawat, Intan (Diponegoro Journal of Management, 2024)
ABSTRACT Compensation satisfaction plays an important role in employees' motivation and affective commitment to the company they work for. The emergence of commitment to employees reflects the employee's attitude towards their work, where a high level of satisfaction indicates a positive attitude towards work. Employees who have a high level of affective commitment tend to feel emotionally attached to the organization and are more likely to remain employed in the long term and also perform well. This research aims to analyze the influence of compensation satisfaction on employee performance through affective commitment at PT Suara Merdeka. This research uses a questionnaire using a non-probability sampling method using sensus sampling. The research results show that compensation satisfaction has a positive effect on employee performance and that affective commitment plays a mediating role in this relationship. The implication of this research is the importance of companies paying attention to fair compensation policies and fostering employee affective commitment to improve employee performance and retention.